Photoacclimatory and photoprotective responses to cold versus heat stress in high latitude reef corals. Issue 2 (24th January 2017) - Pontasch, Stefanie; Fisher, Paul L.; Krueger, Thomas; Dove, Sophie; Hoegh‐Guldberg, Ove; Leggat, William; Davy, Simon K.
Abstract : Corals at the world's southernmost coral reef of Lord Howe Island (LHI) experience large temperature and light fluctuations and need to deal with periods of cold temperature (<18°C), but few studies have investigated how corals are able to cope with these conditions. Our study characterized the response of key photophysiological parameters, as well as photoacclimatory and photoprotective pigments (chlorophylls, xanthophylls, and β‐carotene), to short‐term (5‐d) cold stress ( 15°C; 7°C below control) in three LHI coral species hosting distinct Symbiodinium ITS2 types, and compared the coral–symbiont response to that under elevated temperature ( 29°C; 7°C above control). Under cold stress, Stylophora sp. hosting Symbiodinium C118 showed the strongest effects with regard to losses of photochemical performance and symbionts. Pocillopora damicornis hosting Symbiodinium C100/C118 showed less severe bleaching responses to reduced temperature than to elevated temperature, while Porites heronensis hosting Symbiodinium C111* withstood both reduced and elevated temperature. Under cold stress, photoprotection in the form of xanthophyll de‐epoxidation increased in unbleached P. heronensis (by 178%) and bleached Stylophora sp. (by 225%), while under heat stress this parameter increased in unbleached P. heronensis (by 182%) and in bleached P. damicornis (by 286%). The xanthophyll pool size was stable in all species at all temperatures. Our comparative study demonstrates high variability in the bleaching vulnerability of these coral species to low and high thermal extremes and shows that this variability is not solely determined by the ability to activate xanthophyll de‐epoxidation.